[Haskell-beginners] Functions as Applicatives

Imants Cekusins imantc at gmail.com
Mon Aug 22 18:13:30 UTC 2016


.. actually, I got fg wrong. Caught it by changing g to (/ ):


f::Fractional f => f -> f -> f
f = (+)

g::Fractional g => g -> g
g a = a / 2

h::Fractional h => h -> h
h = (* 10)


fg::Fractional a =>     a -> a -> a
fg = f <$> g
{-  fg a b = (a / 2) + b
    fg a = \b -> (a / 2) + b
-}

fgh::Fractional a =>  a -> a
fgh = fg <*> h
{-  fgh a = fg a (a * 10)
    fgh = \a -> fg a (a * 10)
-}

‚Äč
-------------- next part --------------
An HTML attachment was scrubbed...
URL: <http://mail.haskell.org/pipermail/beginners/attachments/20160822/25e8cf31/attachment.html>


More information about the Beginners mailing list